2023
DOI: 10.3390/ijms24119223
|View full text |Cite
|
Sign up to set email alerts
|

Current Drug Development Overview: Targeting Voltage-Gated Calcium Channels for the Treatment of Pain

Abstract: Voltage-gated calcium channels (VGCCs) are targeted to treat pain conditions. Since the discovery of their relation to pain processing control, they are investigated to find new strategies for better pain control. This review provides an overview of naturally based and synthetic VGCC blockers, highlighting new evidence on the development of drugs focusing on the VGCC subtypes as well as mixed targets with pre-clinical and clinical analgesic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 201 publications
0
4
0
Order By: Relevance
“…Ca v 2.1 α 1 null mutant mice demonstrated pro-nociceptive responses to inflammatory and Neuropathic Pain (NP) models but anti-nociceptive responses to noxious heat stimuli. In a separate study, mice with a spontaneous mutation in the Ca v 2.1 channel, which reduced the activation voltage sensitivity, showed hypoalgesic responses to heat, mechanical, and chemical stimuli [34]. Recently, a GOF mutation in the CACNA1A gene has been linked to trigeminal neuralgia, as mentioned in Table 1.…”
Section: Cacna1a and Cacna1bmentioning
confidence: 98%
See 2 more Smart Citations
“…Ca v 2.1 α 1 null mutant mice demonstrated pro-nociceptive responses to inflammatory and Neuropathic Pain (NP) models but anti-nociceptive responses to noxious heat stimuli. In a separate study, mice with a spontaneous mutation in the Ca v 2.1 channel, which reduced the activation voltage sensitivity, showed hypoalgesic responses to heat, mechanical, and chemical stimuli [34]. Recently, a GOF mutation in the CACNA1A gene has been linked to trigeminal neuralgia, as mentioned in Table 1.…”
Section: Cacna1a and Cacna1bmentioning
confidence: 98%
“…Ca v 2.2 (N-type) VGCCs are present in the dendritic shafts and presynaptic terminals of neurons in both the central and peripheral nervous systems. They are responsible for transmitting nociceptive signals in the spinal cord's dorsal horn from A-δ and C nerve fibers [34]. Several studies have demonstrated that blocking or deleting Ca v 2.2 channels can alleviate pain.…”
Section: Cacna1a and Cacna1bmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not measure the activity of inflammation and pain in the joint as the study was focused on the cartilage integrity; however, it would be interesting to investigate the effects of VGCC on the inflammatory responses and pain relief in the future studies. The action of L-Type VGCC inhibitors might be associated with their systemic activity in neuropathic pain, mediated through the spinal cord, or activities in different brain locations; therefore, a mechanical allodynia behavior test can provide additional information in future studies [ 59 , 60 ].…”
Section: Study Limitationmentioning
confidence: 99%